Pengaruh Play Therapy terhadap Kemampuan Interaksi Sosial Anak Diseleksia di Kelas 1 Ustman Bin Affan - Sufi, Arya Shintya Mutia; Mais, Asrorul; Prystiananta, Nostalgianti Citra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to determine the effect of play therapy on the social interaction skills of first-grade dyslexic children, Ustman bin Affan, at Harapan Umat Elementary School in Jember. This study used a single-subject research (SSR) method with an A-B design, with (A) as the baseline condition and (B) as the intervention condition or condition after treatment. The target behavior in this study was the social interaction skills of children with dyslexia. Researchers analyzed the research data using within-condition and between-condition analysis techniques. The results showed that play therapy can impact the social interaction skills of dyslexic children, with the percentage of subjects' scores increasing from 43.8% before treatment to 72.8% after undergoing play therapy. Therefore, the implementation of play therapy can impact the social interaction skills of dyslexic children by helping them improve their ability to build interactions with their surroundings. Keywords: Dyslexic Children, Social Interaction Skills, Play Therapy